Epidemiological characteristics of patients with invasive pulmonary aspergillosis infected with Aspergillus fumigatus from a tertiary hospital in Ningxia, China - Yuting Kang; Qiujie Li; Wanting Ma; Chao Xu; Wei Jia; Pengtao Wang (Scientific Reports)
Abstract Invasive pulmonary aspergillosis (IPA) is a severe fungal infection primarily caused by Aspergillus fumigatus, representing a significant burden on public health. This study aims to address the limitations in the epidemiological characteristics, risk factors and diagnostic approaches for IPA by identifying clinical characteristics, laboratory findings, and chest CT imaging features that distinguish IPA from Aspergillus fumigatus colonization (AFC). We conducted a retrospective analysis of 249 hospitalized patients, including 77 with IPA and 172 with AFC, at Ningxia Medical University General Hospital from January 2018 to December 2023. Our findings revealed that patients with IPA exhibited higher rates of hemoptysis, dyspnea, and fever compared to those with AFC. Laboratory results indicated elevated levels of galactomannan (GM), white blood cell count (WBC), erythrocyte sedimentation rate (ESR), and platelet count in IPA patients. Chest computed tomography imaging studies showed higher incidences of cavity, consolidation, ground-glass opacity, and halo sign in IPA patients. Voriconazole was the primary treatment for 75.3% of IPA patients, who also had longer hospital stays and higher treatment costs. Multivariate logistic regression identified GM, ESR, chronic obstructive pulmonary disease (COPD), and hypertension as significant risk factors for IPA. Our study highlights the necessity of developing enhanced diagnostic models that integrate GM and ESR biomarkers to improve the specificity and sensitivity of IPA diagnosis. These findings provide valuable insights for early diagnosis and optimized treatment strategies, potentially improving patient outcomes and reducing healthcare costs.